Electrospun ternary composite metal oxide fibers as an anode for lithium-ion batteries - Ling, Jin Kiong; Karuppiah, Chelladurai; Das, Santanu; Izan Izwan, Misnon; Mohd Hasbi, Ab. Rahim; Yang, Chun-Chen; Jose, Rajan (Frontiers Media S.A., 2022)
Nickel–cobalt–manganese oxides (NCMs) are widely investigated as cathode materials for lithium-ion batteries (LIBs) given their beneficial synergistic effects of high storability, electrical conductivity, and stability. However, their use as an anode for LIBs has not been adequately addressed. NCM nanofibers prepared using the multi-needle electrospinning technique are examined as the anode in LIBs. The NCM nanofibers demonstrated an initial discharge capacity of ∼1,075 mAh g−1 with an initial capacity loss of ∼42%. Through controlling the conductive additive content, the initial discharge capacity can be further improved to ∼1810 mAh g−1, mostly attributing to the improved interfiber connectivity supported by the significant lowering of impedance when the amount of conductive additive is increased. This study also reveals that the conventional ratio of 80:10:10 wt% (active materials:additives:binder) is not optimal for all samples, especially for the high active surface area electrospun nanofibers.